Strategy (Business) Using Instagram Social Media @Ruang_Youthforia - Mukhlish Muhammad Maududi; Arif Widodo Nugroho; Vina Aulia Syaharani; Hanifah Mardiah (Universitas Muhammadiyah Prof. DR HAMKA., 2023)
This research is intended to find out and obtain an overview of the strategies created by ruang_youthforia to increase the number of followers who become segmentation or target market who will become users of services or products from ruang_youthforia. This type of research is a type of case study research, using a qualitative approach with the constructivism paradigm to obtain in-depth results based on the real conditions and situations of what is on the ground. Data collection techniques that researchers use by conducting observations, interviews, and documentation. Research conducts data analysis by examining data obtained from observations, interviews, and documentation. To test the validity of the data, researchers conducted by comparing, unifying, and combining all the data that has been obtained results from this study, formulating whether ruang_youthforia has carried out marketing strategies to increase the number of followers that will be analyzed using integrated marketing communication strategies that include Promotion (promotion), Public Relations (Public Relations), Advertising, Direct Marketing, Personal selling, Publicity, Event, Interactive Marketing to communicate its vision and mission,